2017
DOI: 10.17219/dmp/75873
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of pit and fissure sealants on permanent teeth after several etching protocols: In vitro study

Abstract: Background. The pit and fissure areas are 8 times more vulnerable to caries; consequently, sealants have been proven to be efficient. Acid etching is the standard procedure for enamel etching; however, it leaves a demineralized surface. Laser Er:YAG is a good etching alternative due to its properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…(51) However, SBS results of the three groups are considered acceptable and capable of withstanding masticatory forces, as they all exceed the minimum SBS (5.9-7.8) MPa suggested by Reynolds. (52) Similar results were reported by Mézquita-Rodrigo et al, in 2017 (53) who found the highest SBS with conventional acid etching when compared to self-etching adhesive and laser. There was significant difference between conventional acid etching and Er: YAG laser.…”
Section: Discussionsupporting
confidence: 79%
“…(51) However, SBS results of the three groups are considered acceptable and capable of withstanding masticatory forces, as they all exceed the minimum SBS (5.9-7.8) MPa suggested by Reynolds. (52) Similar results were reported by Mézquita-Rodrigo et al, in 2017 (53) who found the highest SBS with conventional acid etching when compared to self-etching adhesive and laser. There was significant difference between conventional acid etching and Er: YAG laser.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous ex vivo dentistry studies are conducted to assess the physical, chemical and biological features of various materials in order to implement the results in dental practice. [1][2][3][4][5] In order to obtain reliable results in such research, the tested materials or tooth samples should be properly prepared and stored.…”
Section: Introductionmentioning
confidence: 99%